THE IMPORTANCE OF USING STEAM EDUCATION IN TEACHING CHEMISTRY IN GENERAL SECONDARY SCHOOLS - Shernazarov Iskandar Ergashovich (Web of Journals Publishing, 2023)
The article highlights the importance of using Steam education in teaching chemistry in secondary schools, the use of Steam education to perform laboratory and practical classes in chemistry, teaching students to perform project work using Steam education, the formation of students' scientific and practical competencies using STEAM education
Keywords: STEAM, Science, technology, engineering, art, mathematics.